Bone marrow aplasia in haemophilia A with hepatitis C and human immunodeficiency virus co-infection — a case report - Shabneez Hussain; Izza Hussain; Aqsa Ashfaq; Laila Abdul Karim; Shoukat Mirza; Hasnain Zafar (Journal of the Pakistan Medical Association, 2022)
Haemophilia A is an inherited bleeding disorder caused due to the deficiency of factor VIII. This case report of a 17-year-old HA boy co-infected by hepatitis C (HCV) and human immunodeficiency virus (HIV) followed by bone marrow aplasia seeks to address the key clinical question of the causality and management of bone marrow aplasia in a resource-constrained setting. Our patient developed pancytopenia which prompted the diagnosis and management of HCV and HIV. Bone marrow biopsy revealed severe aplasia. He was treated with highly active antiretroviral therapy (HAART). Two years later, he developed septic arthritis and haemarthrosis of the elbow and knee joints. He underwent arthrotomy of the knee joint. The patient expired, postoperatively, due to septic shock. This case underlines the need for truly universal access to virally inactivated replacement therapy to prevent complications secondary to infections transmitted by transfusion.